Increase in Drug Overdose Deaths Involving Fentanyl—Rhode Island, January 2012–March 2014. Issue 3 (6th March 2017) - Mercado, Melissa C; Sumner, Steven A; Spelke, M Bridget; Bohm, Michele K; Sugerman, David E; Stanley, Christina
Abstract: Objective: This study identified sociodemographic, substance use, and multiple opioid prescriber and dispenser risk factors among drug overdose decedents in Rhode Island, in response to an increase in overdose deaths (ODs) involving fentanyl. Methods: This cross-sectional investigation comprised all ODs reviewed by Rhode Island's Office of the State Medical Examiners (OSME) during January 2012 to March 2014. Data for 536 decedents were abstracted from OSME's charts, death certificates, toxicology reports, and Prescription Monitoring Program (PMP) databases. Decedents whose cause of death involved illicit fentanyl (N = 69) were compared with decedents whose causes of death did not involve fentanyl (other drug decedents; N = 467). Results: Illicit-fentanyl decedents were younger than other drug decedents ( P  = 0.005). While more other-drug decedents than illicit fentanyl decedents had postmortem toxicological evidence of consuming heroin (31.9% vs 19.8%, P  < 0.001) and various pharmaceutical substances ( P  = 0.002–0.027), third party reports indicated more recent heroin use among illicit fentanyl decedents (62.3% vs 45.6%, P  = 0.002). Approximately 35% of decedents filled an opioid prescription within 90 days of death; of these, one-third had a mean daily dosage greater than 100 morphine milligram equivalents (MME/day). Most decedents' opioid prescriptions were filled at one to two dispensers (83.9%) and written by one to two prescribers (75.8%). Notably, 29.2% of illicit fentanyl and 10.5% of other drug decedents filled prescriptions for buprenorphine, which is used to treat opioid use disorders. Conclusions: Illicit-fentanyl deaths frequently involved other illicit drugs (e.g., cocaine, heroin). The proportion of all decedents acquiring greater than 100 MME/day prescription dosages written and/or filled by few prescribers and dispensers is concerning. To protect patients, prescribers and dispensers should review PMP records and substance abuse history prior to providing opioids.